Security Analysis and Improvements of Session Key Establishment for Clustered Sensor Networks. (30th June 2016) - Kim, Jiye; Moon, Jongho; Jung, Jaewook; Won, Dongho
Abstract : WSN (wireless sensor network) is one of the main technologies in IoT (Internet of Things) applications or services. To date, several schemes have been proposed to establish a pair-wise key between two nodes in WSN, and most of them are designed to establish long-term keys used throughout the network lifetime. However, in the near future, if WSN will be used for information infrastructures in various fields such as manufacturing, distribution, or public facilities management and its life cycle can be as long as that of other common networks, it will definitely be advantageous in terms of security to encrypt messages using session keys instead of long-term keys. In this paper, we propose a session key establishment scheme for clustered sensor networks that is based on elliptic curve Diffie-Hellman (ECDH) key exchange and hash chain. The proposed scheme eliminates vulnerabilities of existing schemes for WSN and has improved security. The proposed scheme is efficient in terms of energy costs compared to related schemes.